Aprendizagem significativa no ensino de química : experimentação e problematização na abordagem do conteúdo Polímeros - Santos, Graziane Gomes dos (2017)
This research aimed to identify, through a didactic sequence, how the students of the third grade of High School learn about concepts related to the content Polymers. We used as a theoretical referential the Theory of Meaningful Learning of David P. Ausubel, as well as considerations on multiculturalism in the teaching of sciences and methodological pluralism in relation to the seven knowledges that are necessary for the education of the future. The research methodology is part of a qualitative approach, using elements of content analysis, based on experimental activities in the classroom . The students participating in the research comprised two groups: group 01, composed of students from a private school; and group 02, by students of a public school. The data collection made it possible to initially assess the students' previous knowledge about the content in question. After that, the activities in didactic sequence (SD) were developed and the students' discursive textual analysis was carried out, through the answers of the questions and a final test. From the analyzes, it was verified that SD contributed to an effective assimilation of the content Polymers and, therefore, to the process of student learning and training of more critical citizens.